Islam and Bioethics: Concerns, Challenges, and Responses (American Journal of Islam and Society, 2006)
On 27-28 March 2006, Pennsylvania State University hosted an internationalconference on “Islam and Bioethics: Concerns, Challenges, and Responses.”Cosponsored by several academic units in the College of Liberal Arts, theconference brought in historians, health care professionals, theologians, and social scientists from ten different countries. Twenty-four papers were presented,along with Maren Grainger-Monsen’s documentary about an Afghaniimmigrant seeking cancer treatment in California.After opening remarks by Susan Welch (dean, College of Liberal Arts)and Nancy Tuana (director, Rock Ethics Institute), panelists analyzed“Critical Perspectives on Islamic Medical Ethics.” Hamada Hamid’s (NewYork University Medical School) “Negotiating Autonomy and Religion inthe Clinical Setting: Case Studies of American Muslim Doctors andPatients,” showed that few doctors explore the role of religion in a patient’sdecision-making process. She suggested that they rethink this practice.Hassan Bella (College of Medicine, King Faisal University, Dammam)spoke on “Islamic Medical Ethics: What and How to Teach.” His survey, conductedin Saudi Arabia among medical practitioners, revealed that most practitionersapproved of courses on Islamic ethics but did not know if suchcourses would improve the doctor-patient relationship. Sherine Hamdy’s(Brown University) “Bodies That Belong to God: Organ Transplants andMuslim Ethics in Egypt” maintained that one cannot easily classify transplantpatients’ arguments as “religious” or “secular,” for religious values are fusedtogether with a patient’s social, political, and/or economic concerns.The second panel, “Ethical Decision-Making in Local and InternationalContexts,” provoked a great deal of discussion. Susi Krehbiel (Brown University)led off with “‘Women Do What They Want’: Islam and FamilyPlanning in Tanzania.” This ethnographic study was followed by Abul FadlMohsin Ebrahim’s (KwaZulu University, Durban) “Human Rights andRights of the Unborn.” Although Islamic law is commonly perceived asantagonistic to the UN’s charter on human rights, Ebrahim argues that bothmay be used to protect those who can and cannot fight for their right to dignity,including the foetus. Thomas Eich (Bochum University) asserted in“The Process of Decision Making among Contemporary Muslim ReligiousScholars in the Case of ‘Surplus’ Embryos” that decisions reached by internationalMuslim councils were heavily influenced by local politics and contentiousdecisions in such countries as Germany and Australia.The afternoon panel, “The Fetus and the Value of Fetal Life,” focusedon specific issues raised by artificial reproductive technologies (ARTs).Vardit Rispler-Chaim (Haifa University) presented “Contemporary Muftisbetween Bioethics and Social Reality: Pre-Selection of the Sex of a Fetus asParadigm.” After summarizing social customs and religious literature fromaround the world, she claimed that muftis generally favor pre-selection techniquesand suggested that their reasoning is guided by a general social ...